Holistic Framework and its Dimensions for Egalitarian Implementation of Corporate Social Responsibility - Malagatti, Veda Devanand (Prabandhan: Indian Journal of Management, 2017)
The evaluation of a business should be based on its contributions both in economic terms as well as in social terms to the community. Nowadays, CSR has an effect not only in technological innovations, but indirectly in administration and marketing innovations too. There is an enormous need of immense spiritual and holistic approach based on endurance governance and performance in corporate social responsibility itself, otherwise it will lead to a crisis if there is no turnaround. The research was carried out with 100 companies, comprising of private and public sector companies. The interpretation has been graphed in three components - Satvik, Rajasik, and Tamasik, which is further measured in real terms of high and low level of CSR. The study found that those institutions or organizations which intend to ignore corporate social responsibility as a mere deed will find it difficult in sustaining for longer durations in this dynamic and competitive modern world. The hypotheses have been illustrated and tested proving that CSR is vital for an organization.